Electro-bioremediation of nitrate and arsenite polluted groundwater. (15th February 2021) - Ceballos-Escalera, Alba; Pous, Narcís; Chiluiza-Ramos, Paola; Korth, Benjamin; Harnisch, Falk; Bañeras, Lluís; Balaguer, M. Dolors; Puig, Sebastià
Highlights: Sustainable technology for efficient treatment of nitrate and arsenite. Bioelectrochemical NO 3− reduction to N2 with coulombic efficiency close to 100%. Denitrifying biocathode formed by Sideroxydans sp. resistant to 5 mg As (III) L −1 . Arsenite oxidation catalytically and linked to denitrification by Achromobacter sp. Abstract: The coexistence of different pollutants in groundwater is a common threat. Sustainable and resilient technologies are required for their treatment. The present study aims to evaluate microbial electrochemical technologies (METs) for treating groundwater contaminated with nitrate (NO3 − ) while containing arsenic (in form of arsenite (As(III)) as a co-contaminant. The treatment was based on the combination of nitrate reduction to dinitrogen gas and arsenite oxidation to arsenate (exhibiting less toxicity, solubility, and mobility), which can be removed more easily in further post-treatment. We operated a bioelectrochemical reactor at continuous-flow mode with synthetic contaminated groundwater (33 mg N-NO3 − L −1 and 5 mg As(III) L −1 ) identifying the key operational conditions. Different hydraulic retention times (HRT) were evaluated, reaching a maximum nitrate reduction rate of 519 g N-NO3 − m 3 Net Cathodic Compartment d −1 at HRT of 2.3 h with a cathodic coulombic efficiency of around 100 %. Simultaneously, arsenic oxidation was complete at all HRT tested down to 1.6 h reaching an oxidation rate of up to 90 g As(III) m −3 Net Reactor Volume d -1 . Electrochemical and microbiological characterization of single granules suggested that arsenite at 5 mg L −1 did not have an inhibitory effect on a denitrifying biocathode mainly represented by Sideroxydans sp. Although the coexistence of abiotic and biotic arsenic oxidation pathways was shown to be likely, microbial arsenite oxidation linked to denitrification by Achromobacter sp. was the most probable pathway. This research paves the ground towards a real application for treating groundwater with widespread pollutants. Graphical abstract: Image, graphical abstract